Circ2Traits: a comprehensive database for circular RNA potentially associated with disease and traits - Ghosal, Suman; Das, Shaoli; Sen, Rituparno; Basak, Piyali; Chakrabarti, Jayprokas (Frontiers in Genetics, 2013)
Circular RNAs are new players in regulation of post transcriptional gene expression. Animal genomes express many circular RNAs from diverse genomic locations. A recent study has validated a fairly large number of circular RNAs in human, mouse and nematode. Circular RNAs play a crucial role in fine tuning the level of miRNA mediated regulation of gene expression by sequestering the miRNAs. Their interaction with disease associated miRNAs indicates that circular RNAs are important for disease regulation. We studied the potential association of circular RNAs (circRNA) with human diseases in two different ways. First, the interactions of circRNAs with disease associated miRNAs were identified, following which the likelihood of a circRNA being associated with a disease was calculated. For the miRNAs associated with individual diseases, we constructed a network of predicted interactions between the miRNAs and protein coding, long noncoding and circular RNA genes. We carried out gene ontology (GO) enrichment analysis on the set of protein coding genes in the miRNA- circRNA interactome of individual diseases to check the enrichment of genes associated with particular biological processes. Second, disease associated SNPs were mapped on circRNA loci, and Argonaute (Ago) interaction sites on circular RNAs were identified. We compiled a database of disease-circRNA association in Circ2Traits ( http://gyanxet-beta.com/circdb/ ), the first comprehensive knowledgebase of potential association of circular RNAs with diseases in human.